2022
DOI: 10.1080/10428194.2022.2086249
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of SARS-CoV-2 infection in lymphoma/chronic lymphocytic leukemia patients during the Omicron outbreak

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 15 publications
(33 reference statements)
3
11
0
1
Order By: Relevance
“…At the beginning of the pandemic, the case fatality rate of CLL patients with COVID‐19 was reported to be as high as 33% 5 and declined to 11% in the second wave 8 . In our study, the mortality rate during the Omicron surge is similar to that previously reported during the same period in patients with CLL 2,3 . Our findings are further consistent with the continuously decreased mortality in patients with CLL throughout the later pandemic waves, as noted above.…”
Section: Variable (N = 128) Category Total N (%) Period #1 N (%) Peri...supporting
confidence: 92%
See 3 more Smart Citations
“…At the beginning of the pandemic, the case fatality rate of CLL patients with COVID‐19 was reported to be as high as 33% 5 and declined to 11% in the second wave 8 . In our study, the mortality rate during the Omicron surge is similar to that previously reported during the same period in patients with CLL 2,3 . Our findings are further consistent with the continuously decreased mortality in patients with CLL throughout the later pandemic waves, as noted above.…”
Section: Variable (N = 128) Category Total N (%) Period #1 N (%) Peri...supporting
confidence: 92%
“…8 In our study, the mortality rate during the Omicron surge is similar to that previously reported during the same period in patients with CLL. 2,3 Our findings are further consistent with the continuously decreased mortality in patients with CLL throughout the later pandemic waves, as noted above. The declined mortality may be best explained by better clinical management with the use of pre-exposure prophylaxis of COVID-19 (tixagevimab/cilgavimab) and anti-viral drugs (ritonavirboosted nirmatrelvir and molnupiravir), which were more commonly administrated during the dominance of the BA.2 and BA.5 subvariants.…”
Section: F I G U R Esupporting
confidence: 90%
See 2 more Smart Citations
“…2,17,18 Similar results were shown in additional studies conducted during the Omicron outbreak, which reported hospitalization rates of 26%-43% and mortality rates of 4%-12% in cohorts that included hemato-oncology patients. [19][20][21][22][23] We evaluated factors that were associated with COVID-19 disease severity, using the National Institute of Health criteria. This classification incorporates respiratory parameters to categorize the COVID-19 status.…”
Section: Discussionmentioning
confidence: 99%